CURRENT STATUS AND DEVELOPMENT PROSPECTS OF HOTEL NETWORKS IN UKRAINE - ILNITSKA-GYKAVCHUK, Galina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the essence and advantages of hotel chains. Management of hotel chains takes place on the basis of a franchise agreement, management contract or leasing (rent). The forms of payment according to the franchise agreement have been considered. It has been established that the following hotel chains occupy the leading positions in the world market: Indian OYO, Chinese Jin Jiang, Marriott International (USA). International hotel chains are also represented in Ukraine, but national ones prevail. Among the national chains, the leaders in Ukraine are the Reikartz Hotel Group, Premier Hotels and Resorts, Royal Hotels and SPA Resorts. The trends in the development of hotel chains in Ukraine are: the appearance in Ukraine of world and national economy class brands, the expansion of the list of brands that unite national hotel chains, the dominance of national chains over international ones, the spread of Asian corporations, uneven territorial distribution of enterprises included in chains, exit of national networks to the world level. The problems of the hotel sector of Ukraine are highlighted: due to military operations (suspension of hotels, destruction of establishments, decrease in the number of tourists, disruption of supply chains, inability to work effectively due to the introduction of a curfew, problems with power outages) and general problems (insufficient number of networks due to significant barriers entering the hotel market of Ukraine, low level of related infrastructure development, lack of state and local management bodies for the development of the hospitality sector, lack of guarantees for investment protection in the development of the infrastructure of hospitality enterprises, insufficient level of use of innovative technologies, discrepancy between the level of prices and the quality of hotel services). The main areas of network development are the introduction of innovations, digitalization of hospitality, diversification of services, combination of travel and hotel work, individual approach to the guest, care for the environment, introduction of package services.